The stability of TNT, RDX and PETN in simulated post-explosion soils: Implications of sample preparation for analysis - Yu, H.; DeTata, D.; Lewis, Simon; Nic Daeid, N. (Elsevier, 2016)
Explosives residues in soils may be a useful source of evidence following the detonation of an improvised explosive device (IED), such as a vehicle-borne IED. Soil samples collected from the vicinity of an explosion scene will often be stored for some time prior to analysis, yet explosives residues in soil samples are susceptible to rapid degradation or transformation. Although some research has assessed the use of different storage temperatures with a view to reducing explosives' degradation over time, further research examining the degradation of explosives in soil when stored under a variety of storage conditions is crucial to determine the optimal sample collection and storage procedures for soil containing explosives residues. In this work, three different soils were spiked with solutions of TNT, RDX and PETN and stored either at room temperature, refrigerated or frozen. Samples were extracted over 6 weeks, with additional samples gamma-irradiated or nitrogen purged prior to storage. Experimental results indicate that TNT underwent very rapid degradation at room temperature, attributed to microbial action, whereas PETN and RDX proved to be more stable. Gamma irradiation and nitrogen purging proved of some benefit for mitigating TNT degradation, with lower storage temperatures ultimately proving the most effective method of mitigating degradation.